Utility of SPECT Functional Neuroimaging of Pain - Bermo, Mohammed; Saqr, Mohammed; Hoffman, Hunter; Patterson, David; Sharar, Sam; Minoshima, Satoshi; Lewis, David H. (Frontiers in Psychiatry, 2021)
Functional neuroimaging modalities vary in spatial and temporal resolution. One major limitation of most functional neuroimaging modalities is that only neural activation taking place inside the scanner can be imaged. This limitation makes functional neuroimaging in many clinical scenarios extremely difficult or impossible. The most commonly used radiopharmaceutical in Single Photon Emission Tomography (SPECT) functional brain imaging is Technetium 99m-labelled Ethyl Cysteinate Dimer (ECD), a lipophilic compound with unique pharmacodynamics. It crosses the blood brain barrier and has high first pass extraction proportional to regional brain perfusion at the time of injection. It reaches peak brain activity one minute after injection and then slowly cleared from the brain. This allows for a practical imaging window of one or two hours after injection. In other words, it freezes a snapshot of brain perfusion at the time of injection that is kept and can be imaged later. This allows for designing functional brain imaging studies that do not require the patient to be inside the scanner at the time of brain activation. Functional brain imaging at the time of severe burn wound care is an example. Not only does SPECT allow for imaging of brain activity under extreme pain conditions, but it also allows for imaging of brain activity modulation in response to analgesic maneuvers whether pharmacologic or non-traditional such as virtual reality analgesia. Together with its utility in extreme situations, SPECTS is also helpful in investigating brain activation under typical pain conditions such as experimental controlled pain and chronic pain syndromes.